Casimir self-assembly: A platform for measuring nanoscale surface interactions in liquids - Michaela Hošková; Oleg V. Kotov; Betül Küçüköz; Catherine J. Murphy; Timur O. Shegai (Proceedings of the National Academy of Sciences, 2025)
Self-assembly (SA) plays a pivotal role in nanotechnology, offering cost-effective methods for bottom–up fabrication and providing versatile model systems for investigating fundamental interactions in various bioinspired systems. However, current methods for investigating and quantifying the dynamics of SA systems are limited in their applicability to planar interfaces, particularly in liquid environments. These methods typically rely on analyzing the collective behavior of particle suspensions rather than directly probing the specific interactions between individual particles. Here, we introduce Casimir self-assembly (CaSA) as a platform, integrating colloidal science, nanophotonics, and fluctuational electrodynamics to study long-range interactions and stability in planar SA systems. Using thermal fluctuations as a probe and visible-range Fabry–Pérot resonances as an optical readout, we demonstrate that CaSA enables a direct in situ study of the Casimir–Lifshitz electrostatic interaction. This approach allows us to map stability regimes of colloidal materials by varying ionic strength and identifying conditions for stable assembly and aggregation limits, and moreover is used to measure the surface charge density of an individual colloidal object down to fractions of an electron charge per square nanometer. Our platform overcomes the limitations of current methods, providing an experimental tool for exploring SA dynamics in situ and expanding the understanding of suspension stability in liquids at the single-particle level. With potential for future applications, CaSA is scalable for studying interfacial forces and is adaptable to multivalent electrolytes and biosensing.